Country Processes and Institutional Arrangements for Article 6 Transactions - World Bank (World Bank, Washington, DC, 2021)
Unlike the Kyoto protocol’s clean development mechanism (CDM), Article 6.2 of the Paris Agreement is designed to allow for international cooperation in carbon markets through decentralized governance. Under this article, bilateral or plurilateral cooperation between participating parties can be established through a mutually agreed policy and governance framework and reflected in the agreement between the parties involved. This decentralized architecture requires considerably higher levels of engagement and oversight from participating parties. The context for setting institutions and approval procedures at the domestic level is fundamentally rooted in the country’s national climate strategy and their nationally determined contribution (NDC). A host country will need to establish a detailed Article 6 strategy that guides, but is not limited to, how its participation in Article 6 will help the country achieve its target. This paper forms the starting point, focusing on the institutional requirements to establish the policy and regulatory process that defines and supports the implementation of the potential activity cycle for Article 6.2 activities and transactions; identifies functions required at the national level from the host country’s perspective; and discusses different options to allocate these functions to existing or new institutions. The Article 6.2 activity cycle can build on project cycles under the Kyoto protocol, with an added requirement for the authorization and transfer of mitigation outcomes (MOs). While the entire process can be developed domestically, host countries can also choose to use international crediting programs to register projects and issue units. However, the host country will still be responsible for the Article 6.2 process of authorizing and transferring ITMOs, as well as applying corresponding adjustments. The type of arrangement that a country chooses to adopt affects the type of institutional arrangement and functions of the different bodies involved.